Comparison of Tranexamic Acid and Misoprostol in Reducing Blood Loss During Cesarean Section: Tranexamic Acid vs Misoprostol in Cesarean Section - Parveen, Talat; Quratulain, .; Tahira, Tayyaba; Javaid, Misbah Kausar; Nisa, Sadaf Un; Samina, . (Pakistan Journal of Health Sciences, 2026)
Excessive blood loss during cesarean section remains a major contributor to maternal morbidity and mortality. Various uterotonic and antifibrinolytic agents are used to reduce perioperative hemorrhage, with Tranexamic Acid and Misoprostol being commonly utilized options. However, evidence comparing their effectiveness in reducing intraoperative blood loss is limited. Objectives: To determine whether tranexamic acid or misoprostol is more effective in reducing blood loss during cesarean section. Methods: Between January 2025 and June 2025, this quasi-experimental study was conducted at the Department of Obstetrics and Gynecology, Shahida Islam Medical College, Lodhran. A total of 126 obstetric patients undergoing C-section were allocated into two groups, i.e. Tranexamic Acid group and the Misoprostol group, at the time of anesthesia. Baseline data regarding age, gravida, parity, and abortion history were recorded. Intraoperative mean blood loss was compared by using an independent samples t-test, and p≤0.050 was considered significant. Results: In the Tranexamic Acid group, mean intraoperative blood loss was lower as compared to the Misoprostol group (282.97 ± 82.80 mL vs. 366.68 ± 116.01 mL; p<0.001). Similar results were noted after stratification of gravida, parity, and abortion history. Postoperative hemoglobin and hematocrit decline were also less in the Tranexamic Acid group. Conclusions: Our results suggest that tranexamic acid provides superior control of blood loss during cesarean section when compared with misoprostol. Based on these outcomes, tranexamic acid may be a better choice for prophylactic use to limit intraoperative bleeding in cesarean deliveries.